1999
DOI: 10.1016/s8756-3282(98)00164-1
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity and the elastic properties of cancellous bone

Abstract: This study addresses the possible significance of trabecular connectivity for the mechanical quality of cancellous bone. A total of 141 cubic trabecular bone specimens collected from autopsy material from 56 individuals without any known bone or metastatic diseases were used. Age variation was in the range of 14 -91 years and a wide range of trabecular architecture was found. Each specimen was three-dimensionally reconstructed with a voxel size of either 20 or 25 m. Using the detailed three-dimensional reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
102
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 37 publications
12
102
0
1
Order By: Relevance
“…The mechanical properties of the cancellous bone are significantly correlated with most of the morphological parameters. These results are akin to those in the literature for different human sites, using different architectural analyses and different mechanical characterization methods [5,18,20,31,60]. Yet, the Pearson coefficients obtained for the correlations between the mechanical properties and the 2D or 3D structural parameters are close.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The mechanical properties of the cancellous bone are significantly correlated with most of the morphological parameters. These results are akin to those in the literature for different human sites, using different architectural analyses and different mechanical characterization methods [5,18,20,31,60]. Yet, the Pearson coefficients obtained for the correlations between the mechanical properties and the 2D or 3D structural parameters are close.…”
Section: Discussionsupporting
confidence: 77%
“…It is interesting to note that the trabecular thickness (Tb.Th) appears underestimated in both studies when computed from the 3D MIL method (95 Am and 77 Am in our study), but that the mean direct trabecular thickness (Tb.Th*) and the mean value of the trabecular thickness evaluated these authors are very comparable (138 and 129 Am, respectively). Our values for 3D fractal dimensions (2.6 F 0.19) are higher than those Table 4 Pearson correlation coefficients (r) between the mechanical and architectural anisotropy parameters n = 16 SR ACT 3D analysis (10 Am) [59,60]. The mechanical properties of the cancellous bone are significantly correlated with most of the morphological parameters.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Some studies have proposed that in normal cancellous bone, connectivity has limited value for assessment of elastic properties [23] and strength [25], although a relationship between loss of connectivity and loss of elastic modulus has been reported [25]. It has been suggested that skeletal fragility in vertebral osteoporosis is in part due to a loss of trabecular connectivity [39]; a loss of trabecular elements would increase loads and strain on the remaining trabeculae leading to a reduction in fatigue life.…”
Section: Discussionmentioning
confidence: 99%
“…The connectivity density, which represents the ratio of the connecting holes, vertices (end points), and struts (bridges) in one unit volume, is also presented, which for dry and tapping processes are close to 9 and 6 per mm 3 , respectively. Thomsen et al [30] stated that human bone has a connectivity density less than 12 per mm 3 , and Kabel et al [31] found that in samples of humans between 14 and 91 years old, the connectivity density varied between 1 and 9 with a mean close to 3. The connectivity density measurements, in particular for the tapped structure, are in keeping with those expected for a material designed to resemble the structure of trabecular bone and suggested targets of 7 per mm 3 [1].…”
Section: Porous Structuresmentioning
confidence: 99%